Carta de Etienne Totti a Roberto H. Todd - Todd, Roberto H.; Totti, Etienne (My University, 1924)
Carta relacionada a la Porto Rico Gas Company.
Keywords: Totti, Etienne--Correspondence.; Totti, Etienne--Correspondencia.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.